Use of Landsat TM Imagery in Determining Important Shorebird Habitat in the Outer Mackenzie Delta, Northwest Territories - Gratto-Trevor, C.L. (ARCTIC, 1996)
Landsat Thematic Mapper (TM) imagery was examined to determine important habitats for shorebirds in the outer Mackenzie Delta, Northwest Territories. In June and July 1991 and 1992, 89 ground plots (200 X 200 m) in different habitats were censused for breeding shorebirds. Habitat type in ground plots was determined by observation and compared to the type identified at the site by an unsupervised Landsat classification technique. The most common species of shorebirds breeding in the area were red-necked phalaropes (Phalaropus lobatus) and common snipe (Gallinago gallinago), followed by semipalmated sandpipers (Calidris pusilla), stilt sandpipers (C. himantopus), pectoral sandpipers (C. melanotos), whimbrel (Numenius phaeopus), Hudsonian godwits (Limosa haemastica), lesser golden plovers (Pluvialis dominica), and semipalmated plovers (Charadrius semipalmatus). Long-billed dowitchers (Limnodromus scolopaceus) were rarely seen. Most species were concentrated in areas of low-centre polygons, sedge, and "low terrain" upland tundra (damp and tussocky). However, snipe were most common in dense willow habitat, and semipalmated plovers were found breeding only on sparsely vegetated gravel. Average density of breeding shorebirds in low-centre polygon or "pure" sedge habitat was 82 pairs per sq km in 1991 (SD=73.8), and 49 in 1992 (SD=49.5). Although the Landsat TM imagery analysis used here correctly identified habitat types near the original, intensively surveyed ("ground-truthed") area, it often misidentified habitats at some sites 10 to 30 km away, probably because of irregular flooding and subtle year-to-year differences in water levels in the active outer delta, and edge habitats too narrow to be distinguished by the satellite imagery. However, the technique can identify potential shorebird habitat roughly, and at least eliminate obviously unsuitable areas in large regions of the Arctic. On a examiné des images prises avec le capteur TM Landsat, afin de déterminer quels sont les habitats importants pour les oiseaux ...